2022
DOI: 10.34067/kid.0001292022
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Contributes to the Immune Mechanisms of Hypertension

Abstract: Hypertension is the leading cause of cardiovascular disease and the primary risk factor for mortality worldwide. For over half a century, researchers have demonstrated that the immunity plays an important role in the development of hypertension; however, the precise mechanisms are still under investigation. The current body of knowledge indicates that pro-inflammatory cytokines may play an important role in contributing to immune-related pathogenesis of hypertension. Interferon gamma (IFNγ), in particular, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 121 publications
1
12
0
Order By: Relevance
“…Based on its role in the immune system, the expression level of this gene can affect the immune response. Another gene optimized here that has a role in the immune system is the IFNG ( IFN-γ ) gene [25][26]. The other selected gene is TNF or TNF-α , which is believed to have pathogenetic and therapeutic applications [27].…”
Section: Resultsmentioning
confidence: 99%
“…Based on its role in the immune system, the expression level of this gene can affect the immune response. Another gene optimized here that has a role in the immune system is the IFNG ( IFN-γ ) gene [25][26]. The other selected gene is TNF or TNF-α , which is believed to have pathogenetic and therapeutic applications [27].…”
Section: Resultsmentioning
confidence: 99%
“…In our identified pathways, the “Immune System” is prominent in the development of hypertension [ 65 ]. The “interferon gamma signaling” pathway modulates immune responses as well as influences hypertension [ 66 ]. The “T cell receptor signaling” and “Apoptosis” pathways are involved in diabetes progression [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, splenic CD8Ts from hypertensive mice can generate salt sensitive hypertension in recipients (97). We further found the cytokine IFNγ was critical for this infiltration to take place in the DOCA + Salt model (10) and adoptive transfer models of hypertension (22). Of note, IFNγ from CD8 + Ts stimulates the IFNγ receptor expressed within the distal convoluted tubule to promote interaction between the CD8 + T and tubule (10).…”
Section: Adaptive Immunity and The Kidney In Hypertensionmentioning
confidence: 98%
“…We further demonstrated that IFNγ is critical for mediating CD8 + T cell infiltration and interaction within the kidney, driving increased sodium retention ( 10 ). Adoptive transfer of primary CD8 + T cells from hypertensive mice is able to induce salt sensitivity hypertension(SSH) in WT mice, however, adoptive transfer of primary CD8 + T cells from IFNγ KO hypertensive mice failed to induce SSHTN in WT mice ( 22 ). Collectively these data evidence the critical role of IFNγ in mediating immune-driven hypertension.…”
Section: Immunity Inflammation and Hypertensionmentioning
confidence: 99%